2002
DOI: 10.1161/01.res.0000014966.97486.c0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Na + -H + Exchange Prevents Hypertrophy, Fibrosis, and Heart Failure in β 1 -Adrenergic Receptor Transgenic Mice

Abstract: Abstract-Chronic stimulation of the ␤ 1 -adrenergic receptor leads to hypertrophy and heart failure in ␤ 1 -adrenergic receptor transgenic mice and contributes to disease progression in heart failure patients. The cellular mechanisms underlying these detrimental effects are largely unknown. In this study, we have identified the cardiac Na ϩ -H ϩ exchanger (NHE1) as a novel mediator of adrenergically induced heart failure. ␤ 1 -Adrenergic receptor transgenic mice showed upregulation of both NHE1 mRNA (ϩ140Ϯ6%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
104
0
12

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 193 publications
(124 citation statements)
references
References 41 publications
8
104
0
12
Order By: Relevance
“…However, recent studies have shown that longer-term treatment with NHE1 inhibitors might protect against cardiac hypertrophy and heart failure. 47,48 One concern about longterm therapy using these inhibitors is the possibility that compensation might occur that would lessen the therapeutic benefits. The apparent upregulation of NHE1 in response to treatment of normal rats with NHE inhibitors raises the possibility that cardiac injury might be enhanced if myocardial infarction were to occur just after the inhibitor was withdrawn.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have shown that longer-term treatment with NHE1 inhibitors might protect against cardiac hypertrophy and heart failure. 47,48 One concern about longterm therapy using these inhibitors is the possibility that compensation might occur that would lessen the therapeutic benefits. The apparent upregulation of NHE1 in response to treatment of normal rats with NHE inhibitors raises the possibility that cardiac injury might be enhanced if myocardial infarction were to occur just after the inhibitor was withdrawn.…”
Section: Discussionmentioning
confidence: 99%
“…136 However, in ␤ 1 -receptor transgenic mice NHE1 is upregulated, and pharmacological NHE1 inhibition prevented the development of hypertrophy, fibrosis, and heart failure. 137 The mechanisms of the protective effects of NHE1 inhibition, the roles of intracellular sodium and calcium, and NHE1 regulation remain to be investigated. 137,138 Apoptosis ␤-Receptor stimulation causes apoptosis of isolated rat cardiomyocytes.…”
Section: Sodium Proton Exchanger Nhe1mentioning
confidence: 99%
“…137 The mechanisms of the protective effects of NHE1 inhibition, the roles of intracellular sodium and calcium, and NHE1 regulation remain to be investigated. 137,138 Apoptosis ␤-Receptor stimulation causes apoptosis of isolated rat cardiomyocytes. Different approaches demonstrate proapoptotic effects of ␤ 1 and antiapoptotic effects of ␤ 2 -receptors.…”
Section: Sodium Proton Exchanger Nhe1mentioning
confidence: 99%
“…Quantification of left ventricular fibrosis was achieved by Sirius red staining followed by semiautomated image analysis, as described. 6 …”
Section: Morphological Analysismentioning
confidence: 99%